Genomic sequencing reveals a positive correlation between the kinetics of strand-specific DNA demethylation of the overlapping estradiol/glucocorticoid-receptor binding sites and the rate of avian vitellogenin mRNA synthesis. - Saluz, H P (1986)
Genomic sequencing was used to study the extent of cytosine methylation of four CpG sites within the regulatory region of the estradiol-inducible avian vitellogenin II gene. Three of these sites, two of which lie within the estradiol-receptor binding site and one in a short stretch of alternating purines and pyrimidines, were initially fully methylated. Analysis of DNA isolated from liver nuclei revealed that hormone treatment of immature White Leghorn roosters resulted in a demethylation of these sites, which occurred initially in only one DNA strand. This demethylation correlated well with the induction of vitellogenin mRNA synthesis. The demethylation of the complementary DNA strand lagged approximately equal to 24 hr behind. The fourth CpG, located within an overlapping glucocorticoid-receptor binding site, was already hemimethylated at the onset of the experiment. The demethylation of this site also occurred with kinetics similar to the rate of vitellogenin mRNA synthesis. All four CpGs remained demethylated even after cessation of gene transcription. A comparison of the methylation state of these four sites in DNA from different tissues demonstrated a clear dependence of the demethylation on estradiol. Our results suggest that this hormone-dependent event occurs via an active pathway through excision repair and/or enzymatic demethylation.